Dialog Teologi dan Perdamaian: Studi tentang Perjumpaan Islam dan Kristen di Timur Tengah - Pricillia Elisabet Siahaan; Putri Natalia Sihite; Tia Devita; Irfan Firma Tua Berutu (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Theological dialogue between Islam and Christianity in the Middle East is a strategic effort to create peace amidst the historical, social and political tensions that plague the region. This research aims to analyze the dynamics of theological dialogue and its impact on interreligious relations, as well as evaluate the challenges and opportunities that arise in the context of peace. Using descriptive-analytical qualitative methods, this research collected data from literature studies, interviews with religious figures, and analysis of interfaith documents.